2002
DOI: 10.1006/ecss.2001.0855
|View full text |Cite
|
Sign up to set email alerts
|

Can Thin-lipped Mullet Directly Exploit the Primary and Detritic Production of European Macrotidal Salt Marshes?

Abstract: Juveniles and adults (>100 mm) of Liza ramada colonize macrotidal salt marsh creeks of Mont Saint-Michel bay (France) between March and November, during spring tide floods (43% of the tides) and return to coastal waters during the ebb. This fish species actively feeds during its short stay in the creek (from 1 to 2 h). On average, each fish swallows sediment including living and inert organic matter, which amounts to 8% of its fresh body weight. Their diet is dominated by small benthic items (especially diatom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
58
3
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 45 publications
7
58
3
2
Order By: Relevance
“…Inconsistency between habitat electivity and osmoregulatory skills was probably due to the combination of an off-shore reproductive migration (Brusle, 1981;Laffaille et al,, 2002) and the reshuf-fling of part of the population among the estuaries once the sand bars that closed the mouths of the estuaries in spring and summer were removed by freshwater run-off in autumn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inconsistency between habitat electivity and osmoregulatory skills was probably due to the combination of an off-shore reproductive migration (Brusle, 1981;Laffaille et al,, 2002) and the reshuf-fling of part of the population among the estuaries once the sand bars that closed the mouths of the estuaries in spring and summer were removed by freshwater run-off in autumn.…”
Section: Discussionmentioning
confidence: 99%
“…Grey mullet (Osteichthyes, Mugilidae) commonly inhabit tropical and warm-temperate estuaries (McDowall, 1988;Blaber, 1997;Pombo et al, 2005), where they play a crucial ecological role (Laffaille et al, 1998(Laffaille et al, , 2002Torras et al, 2000;Cardona et al, 2001;Almeida, 2003) and usually support artisanal fisheries (McDowall, 1988;Blaber, 1997). Although these species always spawn at sea, they are highly euryhaline and thrive in a wide range of salinities (McDowall, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, only a few fish species are able to assimilate salt marsh primary production directly or indirectly; this is the case for mullets Liza and Mugil spp., sand gobies Pomatoschisus spp. and sea bass Dicentrarchus labrax in the MontSaint-Michel Bay (Laffaille et al, 1998(Laffaille et al, , 2002. Salt marsh primary production is essentially assimilated by many invertebrates, and especially by Orchestia gammarella and mysids in European salt marshes (Zagursky and Feller, 1985;Créach et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Since the introduction of the outwelling concept (Odum, 1968), which states that tidal events export detrital organic matter produced in salt marshes to marine waters, strong evidence has also indicated that the export of organic matter from terrestrial to aquatic systems supports secondary production (Loneragan et al, 1997;Kurata et al, 2001). Consequently, salt marshes generally have a very high conservation value, directly as a result of their species complement and because of their role as a feeding ground for migrant birds (Norris et al, 1997;Lefeuvre et al, 2000), and fish, especially juveniles (Boesch and Turner, 1984;Laffaille et al, 2001Laffaille et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Liza carinata commonly inhabit tropical and warm-temperate estuaries (McDowall, 1988;Blaber, 1997;Pombo et al, 2005). Laffaille et al, 1998;Laffaille et al, 2002;Torras et al, 2000;Cardona, 2001;and Almeida, 2003 indicated that mugilidae play a crucial ecological role where this fish community appears to be particulate organic matter transporter and could play a significant role in the global energy budgets of environment. This fish are valuable food sources and ecologically important as primary consumer at coastal and estuarine food chains, and also very representative species for rearing in fish farms (El-Halfawy, 2004;Katsugawa et al, 2006).…”
Section: Introductionmentioning
confidence: 99%